Fluorescent cross-linked polystyrene perylenebisimide/oligo(p-phenylenevinylene) microbeads with controlled particle size, tunable colors, and high solid state emission - Sonawane, Swapnil L.; Asha, S. K. (ACS Applied Materials & Interfaces, 2013)
A series fo cross-linked fluorescent polystyrene (PS) microbeads with narrow size distribution and intense solid state emission was developed. Fluorophores based on perylene bisimide (PBI) and oligo(p-phenylenevinylene) (OPV) designed as acrylic cross-linkers were introduced into the polymerization recipe in a twostage dispersion polymerization, carried out in ethanol in the presence of poly(vinylpyrrolidone) (PVP) as stabilizer. The structural design permitted introduction of up to 10(-5) moles of the fluorophores into the polymerization medium without fouling of the dispersion. The particle size measured using dynamic light scattering (DLS) indicated that they were nearly monodisperse with size in the range 2-3 mu m depending on the amount of fluorophore incorporated. Fluorescence microscope images of ethanol dispersion of the sample exhibited intense orange red emission for PS-PBI-X series and green emission for PS-OPV-X series. A PS incorporated with both OPVX and PBIX exhibited dual emission upon exciting at the OPV wavelength of 350 nm and PBI wavelength of 490 nm, respectively. The low incorporation of fluorophore resulted in almost complete absence of aggregation induced reduction in fluorescence as well as red-shifted aggregate emission. The solid state emission quantum yield measured using integrating-sphere setup indicated a very high quantum yield of phi(powder) = 0.71 for PSOPV-X and phi(powder) = 0.25 for PS-PBI-X series. The cross-linked PS microbeads incorporating both OPV and PBI chromophores had a phi(powder) = 0.33 for PBI emission and phi(powder) = 0.20 for OPV emission. This strategy of introducing fluorophore as crosslinkers into the PS backbone is very versatile and amenable to simultaneous addition of different suitably designed fluorophores emitting at different wavelengths.
Keywords: dispersion polymerization; dual emission; fluorescent cross-linker; oligo(p-phenylenevinylene); Perylenebisimide; solid state fluorescence

Nanostructured donor-acceptor self assembly with improved photoconductivity - Saibal, B.; Ashar, A. Z.; Devi, R. Nandini; Narayan, K. S.; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Nanostructured supramolecular donor-acceptor assemblies were formed when an unsymmetrical N-substituted pyridine functionalized perylenebisimide (UPBI-Py) was complexed with oligo(p-phenylenevinylene) (OPVM-OH) complementarily functionalized with hydroxyl unit and polymerizable methacrylamide unit at the two termini. The resulting supramolecular complex [UPBI-Py (OPVM-OH)](1.0) upon polymerization by irradiation in the presence of photoinitiator formed well-defined supramolecular polymeric nanostructures. Self-assembly studies using fluorescence emission from thin film samples showed that subtle structural changes occurred on the OPV donor moiety following polymerization. The 1:1 supramolecular complex showed red-shifted aggregate emission from both OPV (similar to 500 nm) and PBI (similar to 640 nm) units, whereas the OPV aggregate emission was replaced by intense monomeric emission (similar to 430 nrn) upon polymerizing the methacrylamide units on the OPVM-OH. The bulk structure was studied using wide-angle X-ray diffraction (WXRD). Complex formation resulted in distinct changes in the cell parameters of OPVM-OH. In contrast, a physical mixture of 1 mol each of OPVM-OH and UPBI-Py prepared by mixing the powdered solid samples together showed only a combination of reflections from both parent molecules. Thin film morphology of the 1:1 molecular complex as well as the supramolecular polymer complex showed uniform lamellar structures in the domain range <10 rim. The donor-acceptor supramolecular complex [UPBI-Py (OPVM-OH)](1.0) exhibited space charge limited current (SCLC) with a bulk mobility estimate of an order of magnitude higher accompanied by a higher photoconductivity yield compared to the pristine UPBI-Py. This is a very versatile method to obtain spatially defined organization of n and p-type semiconductor materials based on suitably functionalized donor and acceptor molecules resulting in improved photocurrent response using self-assembly.
Keywords: donor-acceptor; hydrogen bonding; oligo(p-phenylenevinylene); Perylenebisimide; photoconductivity; supramolecular polymeric nanostructures

Random copolyesters containing perylene bisimide: flexible films and fluorescent fibers - Nisha, S. Kumari; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Random copolyesters of poly(L-lactic acid) (PLLA) and [poly-(1,4-cyclohexylenedimethylene-1,4- cyclohexanedicarboxylate)] (PCCD) incorporating varying mol ratios of perylene bisimide (PBI) were developed via a high-temperature solution-blending approach. PCCD incorporating PBI was developed by melt polycondenzation followed by a polyester-polyester transesterification reaction between PCCD PBI and PLLA. The polymers exhibited good solubility in common organic solvents and formed free-standing films, which showed bright red emission upon irradiation with ultraviolet radiation. A solid state fluorescence quantum yield of 10% was observed for this PBI based polyester, which was much higher than that reported in literature for PBI based polymers in the solid state (<1%). Strong red fluorescent nanofibers of these polymers were successfully constructed by electrospinning technique. A random copolyester incorporating donor based on oligo(p-pheneylenevinylene) (OPV) and PBI as acceptor chromophore was also synthesized and fluorescence microscopy images of the electrospun fibers of this polymer exhibited blue, green and red emission upon excitation at different wavelengths. The high temperature solution blending approach involving a high molecular weight polymer and a suitably functionalized it conjugated molecule described here is a unique method by which 1D nanostructures of a wide range of pi-conjugated chromophores could be fabricated having strong fluorescence, with the scope of application in nanoscale optoelectronics, biological devices, as well as sensing.
Keywords: flexible film; fluorescent nanofibers; luminescent film; oligo(p-phenylenevinylene); perylene bisimide

Designed amphiphilic polystyrene as surfactant for oligo(p-phenylenevinylene)-incorporated PS nanobeads and visual detection of bilirubin in human blood serum - Makkad, Sarabjot Kaur; Asha, S. K. (ACS Applied Polymer Materials, 2019)
Amphiphilic polystyrene having pendant glucuronic acid (PS-DGlu) was designed and systematically synthesized to be used as a stabilizing agent in styrene miniemulsion polymerization, while covalently incorporating oligo(p-phenylenevinylene) (OPV)-based fluorophore to prepare PSG-OPV-n. This OPV fluorophore was incorporated with an aim to work as a signal transducer, while glucuronic acid on the surface of PS nanobeads would act as the water solubilizing moiety for PS to enable it to function as surfactant and also serve as an interaction site for free bilirubin to facilitate noncovalent interaction via hydrogen bonding. Efficient energy transfer from OPV to bilirubin was observed, owing to the appreciable spectral overlap between emission of OPV and absorption of bilirubin. Visual color change from blue to bluish green was observed under an UV lamp after the addition of bilirubin into the polymer. Selectivity of the sensor was checked among the pool of other interferences, such as glucose, sucrose, metal ions, cholesterol, and biliverdin. The limit of detection was found to be as low as 20 nM, which is far less than the clinical range for causing jaundice (<25 to >50 mu mol/L). Moreover, the developed sensor showed its effectiveness toward real time monitoring of free bilirubin in human serum.
Keywords: amphiphilic homopolymer; bilirubin; functionalized polystyrene nanobeads; oligo(p-phenylenevinylene); sensing